Stealth Detection System via Multistage Radar and Quantum Radar - Kulshreshtha, Abhijit; Al-Obaidi, Abdulkareem Sh. Mahdi (Universitas Pendidikan Indonesia, 2020)
In todayâ€™s era of advanced weapons and technology development, many remarkable inventions have shifted the balance of war towards the strategically enhanced military equipped with tactical weapons and armaments. One of these strategic advancements is stealth technology due to which stealth aircraft are high in demand for the military. The question that rises is How to detect a stealth object? This paper proposes a novel anti-stealth technique using void detection, high frequency wave interference and neutrino beam propagation. Void detection method uses a modified satellite-based radar that searches for areas in the aerospace from which the transmitted signals sent to the ground receiving station are blocked or deflected. High frequency wave interference method is used to generate a stellar trajectory of the stealth aircraft at the detected void. Neutrino beam comprises of energy quanta mainly neutrinos, which are able to surpass the absorption or deflection systems in the stealth body of aircraft. This unique phenomenon produces a moving image, which is the precise location of the aircraft in the space. Using these methods, the trajectory of the aircraft is detected which ultimately leads to the detection of the stealth aircraft itself. The newly proposed methods which are theoretically more reliable than the existing methods may not have been tested but the method planning make them practically feasible considering that the technology used is a part of advanced engineering today. Â